Fossil‐Lagerstätten, palaeoecology and preservation of invertebrates and vertebrates from the Devonian in the eastern Anti‐Atlas, Morocco. (18th October 2019) - Frey, Linda; Pohle, Alexander; Rücklin, Martin; Klug, Christian
Abstract : In some Devonian strata in the eastern Anti‐Atlas, fossil invertebrates are abundant, display a high taxonomic diversity and indicate many shifts in palaeoecology. This is reflected in changes in faunal composition of invertebrates and vertebrates. Fossils of jawed vertebrates of late Lochkovian and younger age have been recorded and are relatively common with their abundance and diversity increasing towards the Late Devonian. Environmental changes in the Devonian also left their mark in the preservation of vertebrates and invertebrates from the Anti‐Atlas, which varies strongly through time and regionally. This variation partially reflects environmental changes linked with the evolution of small marine basins during the disintegration of the continental shelf of Gondwana in this region, fluctuations of the regional sea level and other environmental changes. To improve our understanding of these ecological changes, of shifts in preservation through the succession and of the formation of Fossil‐Lagerstätten, we analysed the mineral composition of some invertebrate and vertebrate samples of Devonian and Early Carboniferous age by Raman spectroscopy and X‐ray diffraction. Additionally, we characterized some of these Fossil‐Lagerstätten using palaeontological and sedimentological parameters. We examined eight Devonian Konzentrat‐Lagerstätten and two Konservat‐Lagerstätten with soft‐tissue preservation (the Famennian Thylacocephalan Layer and the Hangenberg Black Shale of the southern Maïder). The last two are the first Konservat‐Lagerstätten described from the Devonian of North Africa. The taphonomic and oceanic settings suggest that these Konservat‐Lagerstätten are formed because of stagnation (related to vertical restriction of water exchange and water depth rather than limited spatial water exchange and a lateral restriction) in the relatively small Maïder Basin with limited water exchange with the neighbouring Tafilalt Basin. The temporally low oxygen levels in the Maïder Basin are a possible reason for the reduced chondrichthyan diversity (missing demersal and shallow water species) compared to the Tafilalt Platform.